FORMULASI UJI AKTIVITAS SEDIAAN GEL FACIAL WASH EKSTRAK DAUN PEDADA (Sonneratia alba Sm.) MENGGUNAKAN METODE DPPH - sulasmi sulasmi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2026)
This study evaluated the potential of pedada leaf extract (Sonneratia alba Sm.) as an active ingredient in a facial cleansing gel preparation. Antioxidant activity was tested using the DPPH method and the gel's physical characteristics were assessed. The results indicate that pedada leaves have potential as a natural antioxidant in gel-based facial cleansing cosmetic formulations. This study used an experimental method with a laboratory approach. Ethanol extract of pedada leaves was obtained through maceration and then formulated into facial wash gels at various concentrations. Evaluations were conducted on the physical properties of the preparation, such as pH, homogeneity, adhesion, spreadability, and viscosity. Antioxidant activity was tested using the DPPH method to determine the IC₅₀ value. The results showed that the facial wash gel preparation with pedada leaf extract met good physical standards, such as pH, viscosity, and homogeneity. The best antioxidant activity was obtained at a specific concentration with an IC₅₀ value of 50 ppm, indicating very strong antioxidant activity and potential for use in natural skin care products. The conclusion of this study indicates that pedada leaf extract can be formulated into a facial wash gel that meets physical standards and has very strong antioxidant activity. This study recommends the use of pedada leaves as a natural active ingredient in cosmetic products, and the need for further research to test long-term stability and safety of use.